Fish Community Structure Of The Bahu River Estuary Manado City: - Sampe, Ayumi Angraini; Manu, Gaspar D.; Kambey, Alex D.; Pratasik, Silvester Benny; Rondonuwu, Arie B.; Rangan, Jety K. (Sam Ratulangi University, 2024)
Community structure is an ecological term to indicate what organisms are present in a given environment, in what numbers, and how they are interconnected, through ecological indices that reflect dominance, evenness, and richness traits. The estuary is the most downstream part of the river and is connected to the sea. The Bahu River estuary is a habitat for a variety of aquatic life, especially fish, where water quality conditions greatly affect the abundance, diversity, and dominance. The methods used in this study were general field survey methods and fishing methods using the